Improving HTTP Caching Proxy Performance with TCP Tap - Maltz, Dave; Bhagwat, Pravin (Proceedings of the Fourth International Workshop on High Performance Protocol Architectures (HIPPARCH'98), 1998)
Application layer proxies are an extremely popular method for adding new services to existing network applications. They provide backwards compatibility, centralized administration, and the convenience of the application layer programming environment. Since proxies serve multiple clients at the same time, they are traffic concentrators that often become performance bottlenecks during peak load periods. In this paper we present an extension of the TCP Splice technique [6] called TCP Tap that promises to dramatically improve the performance of an HTTP caching proxy, just as TCP Splice doubled the throughput of an application layer firewall proxy